Ensinar e Aprender na Évora Medieval - André Filipe Oliveira da Silva (Medievalista)
Preserved by their ecclesiastical sanctuaries, the erudite culture, the writing and reading and school education expand during the Late Middle Ages, with an augmenting supply adapted to its recipients and their motivations. The social mobility that a good education could bring, the needs of an increasingly demanding ecclesiastical hierarchy, the specialization within the central and local administrations, the specificities of the religious minorities, as well as the prestige associated with high culture, are some of the factors responsible for the creation of these new schools. Évora, municipality, episcopal city and frequent stop of the Royal Court, reveals itself as an excellent case study of this late medieval expansion, intimately connected to the dynamics of a growing city.